Studi Perspektif Antropologi Gaya Tari MakYong Muda di Sanggar Ledang Balai Tanjung Pinang - Meilina Meilina; Atina Amalia Shulha; Meina Meina; Denny Eko Wibowo (Indonesian Journal of Performing Arts Education, 2022)
AbstractMak Yong art is a form of Malay traditional art. MakYong dance is theatrical performance art, part of a drama that tells the story of human life. Stories include conversations, dance and acting moves, and scripts for the actors. MakYong comes from several areas that started from Nara Yala, spread to Kelantan, and entered Indonesia. This study aims to determine the study of the Mak Yong Muda dance style in Ledang Balai Studio, Tanjung Pinang, Riau Archipelago. The theory of style studies is linked to the observation of the Mak Yong Dance from the view or perspective of Dance Anthropology. The dance style in question is the emblematic style and the assertive style. This research uses qualitative methods to explore whether there is factual information or events that happened. The results of the research show that Mak Yong Muda presents folklore. Some standards are still not to be removed in the Mak Yong Dance performance in the aspects of dance and script movements. The emblem and assertive styles in the dance seem to influence each other from the actor's story and the dancers at Ledang Balai. Experts, humanists, artists, and residents must contribute to preserving this art. AbstrakKesenian Tari MakYong merupakan salah satu bentuk seni tradisi Melayu. Tari MakYong merupakan seni pertunjukkan teater, bagian dari drama yang menceritakan kisah hidup manusia. Cerita dalam bentuk percakapan, gerak lakon maupun gerak tari, serta naskah tertulis untuk para pelakon. MakYong bersumber dari beberapa daerah yang berawal dari Nara Yala, menyebar ke Kelantan hingga masuk ke Indonesia. Penelitian ini bertujuan untuk mengetahui studi gaya Tari MakYong Muda yang ada di Sanggar Ledang Balai, Tanjung Pinang, Kepulauan Riau. Teori studi gaya dikaitkan ke observasi Tari MakYong dalam pandangan atau perspektif Antropologi Tari. Gaya tari yang dimaksud ialah gaya emblem dan gaya asertif. Penelitian menggunakan metode kualitatif guna menelusuri sendiri apakah terdapat informasi fakta atau kejadian yang benar terjadi. Hasil penelitian diketahui bahwa kesenian MakYong Muda ini membawakan cerita rakyat. Terdapat pakem-pakem yang tidak dihilangkan dalam pertunjukan Tari MakYong pada aspek gerak tari dan naskah. Gaya emblem dan gaya asertif pada tari terlihat saling mempengaruhi dari cerita pelakon dan para penari yang ada di Ledang Balai. Para pakar, budayawan, seniman, dan warga setempat perlu berkontribusi sehingga kesenian ini tetap dilestarikan.